New Generation of Organic Fertilizers - Turan, Metin; Yildirim, Ertan (IntechOpen, 2022)
This book provides a comprehensive overview of organic fertilizers and their importance in sustainable agriculture, biodiversity, and the environment. It presents new approaches, ideas, and trends on how to increase the effectiveness of chemical fertilizers as well as the resistance of plants against biotic and abiotic stress conditions. Chapters address such topics as the benefits of organic fertilizers over their chemical counterparts, vermicomposting, organic farming, insects in organic fertilizer production, and much more.